A comparative analysis of the performance of conventional and Islamic unit trust companies in Malaysia - Md Saad, Norma; Abd. Majid, M. Shabri; Kassim, Salina; Hamid, Zarinah; Mohd. Yusof, Rosylin (Emerald Group Publishing, 2010)
Purpose – The purpose of this paper is to investigate the efficiency of selected conventional and Islamic unit trust companies in Malaysia during the period 2002 to 2005. Design/methodology/approach – The paper adopts Data Envelopment Analysis (DEA) to investigate efficiency, as measured by the Malmquist index, which is decomposed into two components: efficiency change and technical change indexes. Findings – The study indicates that technical efficiency is the main contributor to enhancing the efficiency of the Malaysian unit trust industry. In addition, the larger the size of the unit trust companies, the more inefficient the performance. In comparing the efficiency of unit trust companies, the study finds that some of the Islamic unit trust companies perform better than their conventional counterparts. Research limitations/implications – The study is limited to five Islamic unit trust companies. Thus, the findings of this study are indicative, but inconclusive for the unit trust industry as a whole. Practical implications – The results have two important implications for both conventional and Islamic unit trust companies in Malaysia. First, the deterioration of total factor productivity (TFP) in the unit trust industry in Malaysia is due to the deficiency of innovation in technical components. Second, the size of the unit trust companies has an adverse effect on the TFP performance. Originality/value – The contribution of this study is that it analyzes the efficiency of the two types of unit trust industry which are important and relevant for Malaysia. This significance arises from the dual financial system, in which the Islamic unit trust companies operate in parallel with their conventional counterparts. The comparison sheds some light on the performance of the Islamic unit trust companies, whose operations are based on profit-sharing, in contrast to the conventional unit trust companies.